MULTIMEDIA INTERAKTIF BERBASIS POWERPOINT: SOLUSI KREATIF PEMBELAJARAN BAHASA ARAB DI SD MUHAMMADIYAH 1 PEKAJANGAN - Muthia Fiqihhani; Muasomah; Faliqul Isbah; Dzulkifli M. Mooduto (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study aims to develop and evaluate the feasibility of interactive multimedia-based Arabic language learning media using PowerPoint, designed to increase student motivation and participation. The type of research used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model, which refers to the Dick, Carey, and Carey model. Data were collected through interviews, observations, and questionnaires. The results of the study indicate that the developed media contains elements of text, images, animations, and interactive quizzes in .pptx format, which have been validated by media experts with a feasibility score of 87% and material experts 98% (both in the "very feasible" category), while student responses yielded an average feasibility of 86%. The conclusion of this study is that interactive multimedia-based Arabic language learning media using PowerPoint is very feasible to be used as an innovative alternative to improve the quality of learning in grade IV of SD Muhammadiyah 1 Pekajangan.